الاعتماد الايجاري كآلية حديثة لتمويل المؤسسات الناشئة – حالة الجزائر - بوحفص مسعودي; عماد الدين لعجايلية (My University, 2021)
Start-up are today a cornerstone of advanced economic growth strategy through their positive contribution، which is determined by several vital economic metrics، such job creation، GDP growth and domestic exports promotion. However، this type of endeavor still faces significant challenges.The problem of financing، to which we will try to address this research as we have tried to shed light on the financing formula by leasing as a new technology for financing، particularly in Algeria as a result of its development and role in development، and perhaps one of the most important and important challenges. This form has been referred to in a range of notions، benefits and various sorts. We also touched on the experience of Algeria in adopting this formulation in spite of its short life، and a range of judgments and legislation regulating this formulation. ........................................................... .تعد الشركات الناشئة اليوم حجر الزاوية في استراتيجية النمو الاقتصادي المتقدم من خلال مساهمتها الإيجابية، والتي يتم تحديدها من خلال العديد من المقاييس الاقتصادية الحيوية، مثل خلق فرص العمل ونمو الناتج المحلي الإجمالي وتعزيز الصادرات المحلية. إلا أن هذا النوع من المساعي لا يزال يواجه تحديات كبيرة. مشكلة التمويل، والتي سنحاول أن نتناولها في هذا البحث حيث حاولنا تسليط الضوء على صيغة التمويل عن طريق التأجير كتقنية جديدة للتمويل، خاصة في الجزائر باعتبارها نتيجة لتطورها ودورها في التنمية، ولعل من أهم وأهم التحديات. وقد تمت الإشارة إلى هذا النموذج في مجموعة من المفاهيم والفوائد وأنواع مختلفة. كما تطرقنا إلى تجربة الجزائر في اعتماد هذه الصياغة رغم عمرها القصير، ومجموعة من الأحكام والتشريعات المنظمة لهذه الصياغة.